Pemberdayaan BUMDes dan UMKM Desa Kace Timur Melalui Promosi Produk Berbasis Digital - Darman Saputra; Hamsani Hamsani; Ari Agung Nugroho; Dony Yanuar; Ary Fakturrachman Aryansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In line with the pattern of the community partnership program which is a problem solver, sustainable for the target group of strategic partners economically which includes business management, marketing so that people can live economically independently, moreover BUMDes is also one of the pillars of the village economy, therefore BUMDes must the main tasks and functions are strengthened, one way to do this is by creating or giving a touch of professional management in carrying out every business activity, one of which is the implementation of modern information technology-based marketing management, namely empowering through socialization, education and mentoring wrapped in the program this community partnership. This community partnership program was implemented in East Kace Village, located in West Mendo District, Bangka Regency, Bangka Belitung Islands Province, Indonesia with the target partners being the management or managers of the Berdikari Village-Owned Enterprises. Initial preparations were carried out by coordinating and socializing activities including meetings with village officials, both customary and official, the Village Consultative Body, Community Empowerment Institutions, as well as several lingsir and local community leaders regarding the implementation of this program which includes: objectives, benefits, targets, flow of activities of this community partnership program. Preparation also includes planning the place and facilities and infrastructure needed during the activity process.